2008
DOI: 10.1088/0953-2048/22/1/015027
|View full text |Cite
|
Sign up to set email alerts
|

Significant improvement of critical current density in MgB2doped with ferromagnetic Fe3O4nanoparticles

Abstract: Ferromagnetic Fe3O4-doped MgB2 bulks were first fabricated in this work by the hot pressing method. It was found that Fe3O4 does not react with Mg or B during the fabrication process. Peak Jc values of the 5 wt% Fe3O4-doped MgB2 are higher than 106 A cm−2 in the temperature range 5–30 K. Especially at 30 K, the peak Jc is 1.02 × 106 A cm−2 for the 5 wt% Fe3O4-doped MgB2, the highest values at 30 K found in the literature, and about seven times that of the 5 wt% SiC-doped MgB2 sample. The drop in Jc with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 28 publications
(28 reference statements)
0
12
0
2
Order By: Relevance
“…Iron oxide and its derivative nanoparticle systems have attracted considerable attention because of their potential applications ranging from magnetic recording to cancer research . There are numerous studies performed on undoped and doped Fe 3 O 4 nanoparticle systems, and also on magnetite‐based nanocomposites in an attempt to tune their magnetic and dielectric properties for effective technological and biomedical applications. In conjunction with such technological potentials, there are several unanswered questions regarding their physical properties such as Verwey transition (a transition between conducting and insulating state is called Verwey transition temperature T V (~122 K) where Fe 3 O 4 exhibits conducting state below T V and insulating state above T V ), the onset of ferroelectricity, and magnetodielectric coupling as a function of crystallite geometries and doping in Fe 3 O 4 matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Iron oxide and its derivative nanoparticle systems have attracted considerable attention because of their potential applications ranging from magnetic recording to cancer research . There are numerous studies performed on undoped and doped Fe 3 O 4 nanoparticle systems, and also on magnetite‐based nanocomposites in an attempt to tune their magnetic and dielectric properties for effective technological and biomedical applications. In conjunction with such technological potentials, there are several unanswered questions regarding their physical properties such as Verwey transition (a transition between conducting and insulating state is called Verwey transition temperature T V (~122 K) where Fe 3 O 4 exhibits conducting state below T V and insulating state above T V ), the onset of ferroelectricity, and magnetodielectric coupling as a function of crystallite geometries and doping in Fe 3 O 4 matrix.…”
Section: Introductionmentioning
confidence: 99%
“…carbohydrates [11][12][13], B 4 C [14], carbon-nanotubes [15], SiC [16] has been reported to be effective in improving superconducting properties such as H irr , H c2 and J c under high magnetic fields. In addition to carbon, doping of rare earth oxides [17,18], co-doping of rare earth and carbon [13] and magnetic nanoparticles [19] have also been found to be effective in improving the superconducting properties of MgB 2 . In the case of carbon doping it has been found that carbon substituted at boron sites increases intra-band impurity scattering, leading to an enhancement in H c2 and a decrease in T c .…”
Section: Introductionmentioning
confidence: 99%
“…It was found [11] that in Ho 2 O 3 -doped MgB 2 samples the magnetic HoB 4 impurities are formed, and the significant improvement in flux pinning was observed. The pinning enhancement was also observed by addition of ferromagnetic Fe 3 O 4 [12] and Co 3 O 4 [13] nanoparticles to the raw MgB 2 .…”
Section: Introductionmentioning
confidence: 79%